Physician's knowledge, attitudes, and practices regarding seasonal influenza, pandemic influenza, and highly pathogenic avian influenza A (H5N1) virus infections of humans in Indonesia. Issue 1 (27th October 2016) - Mangiri, Amalya; Iuliano, A. Danielle; Wahyuningrum, Yunita; Praptiningsih, Catharina Y.; Lafond, Kathryn E.; Storms, Aaron D.; Samaan, Gina; Ariawan, Iwan; Soeharno, Nugroho; Kreslake, Jennifer M.; Storey, J. Douglas; Uyeki, Timothy M.
Abstract : Indonesia has reported highest number of fatal human cases of highly pathogenic avian influenza (HPAI) A (H5N1) virus infection worldwide since 2005. There are limited data available on seasonal and pandemic influenza in Indonesia. During 2012, we conducted a survey of clinicians in two districts in western Java, Indonesia, to assess knowledge, attitudes, and practices (KAP) of clinical diagnosis, testing, and treatment of patients with seasonal influenza, pandemic influenza, or HPAI H5N1 virus infections. Overall, a very low percentage of physician participants reported ever diagnosing hospitalized patients with seasonal, pandemic, or HPAI H5N1 influenza. Use of influenza testing was low in outpatients and hospitalized patients, and use of antiviral treatment was very low for clinically diagnosed influenza patients. Further research is needed to explore health system barriers for influenza diagnostic testing and availability of antivirals for treatment of influenza in Indonesia.